Adiponectin reduces thermogenesis by inhibiting brown adipose tissue activation in mice - Qiao, Liping (2014)
AIMS/HYPOTHESIS: Adiponectin is an adipocyte-derived hormone that plays an important role in energy homeostasis. The main objective of this study was to investigate whether or not adiponectin regulates brown adipose tissue (BAT) activation and thermogenesis. METHODS: Core body temperatures (CBTs) of genetic mouse models were monitored at room temperature and during cold exposure. Cultured brown adipocytes and viral vector-mediated gene transduction were used to study the regulatory effects of adiponectin on Ucp1 gene expression and the underlying mechanisms. RESULTS: The CBTs of adiponectin knockout mice (Adipoq(−/−)) were significantly higher than those of wild type (WT) mice both at room temperature and during the cold (4°C) challenge. Conversely, reconstitution of adiponectin in Adipoq(−/−) mice significantly blunted β adrenergic receptor agonist-induced thermogenesis of interscapular BAT. After 10 days of intermittent cold exposure, Adipoq(−/−) mice exhibited higher UCP1 expression and more brown-like structure in inguinal fat than WT mice. Paradoxically, we found that the anti-thermogenic effect of adiponectin requires neither AdipoR1 nor AdipoR2, two well-known adiponectin receptors. In sharp contrast to the anti-thermogenic effects of adiponectin, AdipoR1 and especially AdipoR2 promote BAT activation. Mechanistically, adiponectin was found to inhibit Ucp1 gene expression by suppressing β(3)-adrenergic receptor expression in brown adipocytes. CONCLUSIONS/INTERPRETATION: This study demonstrates that adiponectin suppresses thermogenesis, which is likely to be a mechanism whereby adiponectin reduces energy expenditure.